Buckwheat breeding and production in Russia during the past 100 years - A. N. Fesenko; I. N. Fesenko (Труды по прикладной ботанике, генетике и селекции)
Average buckwheat yield in Russia has increased from 0.49 to 0.94 t/ha (1.9 times) in the period from the 1960s to 2011-2017, which is comparable to the growth of wheat yields for the same period (2.1 times, from 1.18 to 2.42 t/ha). However, if the growth in wheat yields occurred gradually, the entire growth of buckwheat yield falls on the beginning of the 21st century. Such differences in dynamics indicate that the increase in buckwheat yield is not related to the improvements in agricultural technology or climate changes. Nor it is related to any significant changes in the structure of buckwheat sowing regions, as the average yield in the most important region of buckwheat cultivation, Altai Territory, is only 0.91 t/ha (i. e. less than the country’s average). Chronologically, the period of an abrupt increase in the yield of buckwheat in Russia coincides with widespread introduction of cultivars with determinate growth habit (determinants). Since 1999, the share of determinant varieties in the total area under buckwheat in Russia has increased from 8.2 to 56.7%. Apparently, it was a main cause for the significant growth of buckwheat yield in Russia. Determinant cultivars based on the d (det) mutation are characterized by reduced plant height, reduced number of flowers on shoots, and more intensive and fast blossoming of inflorescences (and, consequently, more intensive and fast maturation). The increased morphological potential of productivity (the number of vegetative nodes on the stem and first – order branches) ensures a higher level of yield for these cultivars. At present, our lab is developing determinant buckwheat cultivars using some additional mutations. A major success in this work has been the world’s first determinant cultivar with green flowers (the gc mutation) named ‘Design’, which develops thicker and stronger fruit stalks with higher resistance to seed shattering.